Understanding the Light Detection in an Integrated Novel Electrophotonic Wavesensor Photodetector - Joaquín Hernández-Betanzos; Mariano Aceves-Mijares; Alfredo Abelardo González-Fernández (Applied Sciences, 2022)
This work presents a novel integrable silicon photodetector which can only be conceived as part of a monolithic electrophotonic basic structure formed of a silicon light emitter, waveguide and light detector. That is, it cannot operate as a single electronic or photonic device. The detector presents current gain, and photons reach the depletion region straightforward, allowing the detection of low power light produced by silicon light sources currently in use, which is difficult for existing photodetectors. The waveguide core is made of silicon nitride, and it is simultaneously the insulator in a MOS-like device. The light detection unit is intended for novel seamless electrophotonic platforms, and it is called wavesensor. In spite that the device is a MOS-like structure, it is not a MOSFET neither a lateral bipolar transistor, and one of the main differences with the former is that this is a bulk device working in Punch-Through regime. Being a MOS-like structure, it is fully compatible with standard microelectronics technology. A development of the mathematics involved in its operation is carried out in order to understand the physics of the detector, showing a gain factor in the photocurrent. Computer simulations of the fabrication process and photoelectric response of the device confirmed photocurrent values higher than the expected for a photodiode with efficiency = 1, thus demonstrating a new integrable photodetector with gain, capable of detecting light in the range of nW for electrophotonic applications.